2021
DOI: 10.1002/pros.24278
|View full text |Cite
|
Sign up to set email alerts
|

Stratification of prostate cancer patients into low‐ and high‐grade groups using multiparametric magnetic resonance radiomics with dynamic contrast‐enhanced image joint histograms

Abstract: Purpose: This study aimed to investigate the potential of stratification of prostate cancer patients into low-and high-grade groups (GGs) using multiparametric magnetic resonance (mpMR) radiomics in conjunction with two-dimensional (2D) joint histograms computed with dynamic contrast-enhanced (DCE) images. Methods: A total of 101 prostate cancer regions extracted from the MR images of 44 patients were identified and divided into training (n = 31 with 72 cancer regions) and test datasets (n = 13 with 29 cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In brief, among DCE parameters, the histogram parameters of K trans and k ep can consistently discriminate the aggressiveness of PCa regardless of whether the old GS or new ISUP grading system is used. Recently, Urakami et al [ 14 ] suggested that the integration of mpMRI radiomics with 2D histogram analysis derived from DCE-MRI might stratify patients with PCa into low- and high-risk groups based on their ISUP grades. All of these studies supported the use of DCE parameters as potential predictors for PCa risk stratification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In brief, among DCE parameters, the histogram parameters of K trans and k ep can consistently discriminate the aggressiveness of PCa regardless of whether the old GS or new ISUP grading system is used. Recently, Urakami et al [ 14 ] suggested that the integration of mpMRI radiomics with 2D histogram analysis derived from DCE-MRI might stratify patients with PCa into low- and high-risk groups based on their ISUP grades. All of these studies supported the use of DCE parameters as potential predictors for PCa risk stratification.…”
Section: Discussionmentioning
confidence: 99%
“…Although DCE-MRI may be capable of evaluating the risk of PCa based on GS, the exact correlation between DCE-MRI and the novel ISUP grading system is uncertain because studies investigating this correlation are lacking. Recently, a study on 44 PCa patients with a total of 101 PCa regions proposed that multiparametric MRI (mpMRI) radiomics in conjunction with a two-dimensional (2D) joint histogram generated from DCE images could potentially stratify PCa patients into low- (ISUP grade ≤ II) and high-ISUP grades (ISUP grade ≥ III) [ 14 ], implying that the use of DCE parameters alone may be sufficient for categorizing ISUP grades needing investigation.…”
Section: Introductionmentioning
confidence: 99%
“…It may be that the outer space between the cells was compressed, which limited the diffusion of water molecules, the MRI signal became higher, and the ADC value decreased. With the increase of PCa cell invasion, the adenoid structure gradually became solid and flaky [ 14 , 15 ]. Ogura et al [ 16 ] pointed out that the higher the degree of PCa malignancy, the lower the ADC value, which was consistent with the results of this study.…”
Section: Discussionmentioning
confidence: 99%